Relationship between height and arm span of elderly persons in an urban colony of New Delhi - Anil Kumar Goswami; Mani Kalaivani; Sanjeev Kumar Gupta; Baridalyne Nongkynrih; Chandrakant S Pandav (Indian Journal of Public Health, 2018)
Anthropometric changes take place with increasing age. Progressive loss of height makes it difficult to use height for calculation of body mass index in nutritional screening of elderly persons. There is a need to find other alternative methods which could be used as proxy measurements of height in them. To assess the relationship of height and arm span and among elderly persons. A community-based cross-sectional study was conducted among elderly persons in urban colony of Delhi. Height and arm span of persons aged 60 years and above (n = 711) were measured according to standard methods. Correlation between arm span and height was calculated. The mean arm span was seen to be more than the mean height in all age-groups and both sexes. There was a linear relationship between height and arm-span in all age-groups. There was a strong correlation between arm span and height in all age groups. Arm span could be used instead of height as an alternative in the conventional body mass index in elderly persons.